2020
DOI: 10.3389/fneur.2019.01338
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and Neuroanatomical Account of Impulsivity in Parkinson's Disease

Abstract: Hlavatá et al. Impulsivity in Parkinson's Disease behavioral tests, since various factors may and will influence the ultimate outcomes, be it the lack of sensitivity in specific, limited ICD subtypes, excessive caution of ICD patients during testing due to previous negative experience rendering simplistic tasks insufficient, or other, as of now unknown aspects, calling for further research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 103 publications
0
30
0
Order By: Relevance
“…For example, predictive processing has been linked to activity of a fronto-parietal network that includes prominently the anterior cingulate, striatum, and insula (Ernst and Paulus, 2005; Krain et al, 2006; Balleine et al, 2007; Kuhns et al, 2017; Siman-Tov et al, 2019; Poudel et al, 2020). In addition, pathological conditions that affect decision-making, such as the increased choice impulsivity in Parkinson’s disease (Nombela et al, 2014), have been associated with functional and neuroanatomical abnormalities of the anterior cingulate and striatum (Gescheidt et al, 2013; Ruitenberg et al, 2018; Hlavatá et al, 2019; Kim and Im, 2019). Moreover, neuroimaging, brain-lesion, and stimulation studies have provided evidence for the association of the left inferior parietal cortex with covert attention to an upcoming movement (Rushworth et al, 2001a; Rushworth et al, 2001b; Rushworth et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…For example, predictive processing has been linked to activity of a fronto-parietal network that includes prominently the anterior cingulate, striatum, and insula (Ernst and Paulus, 2005; Krain et al, 2006; Balleine et al, 2007; Kuhns et al, 2017; Siman-Tov et al, 2019; Poudel et al, 2020). In addition, pathological conditions that affect decision-making, such as the increased choice impulsivity in Parkinson’s disease (Nombela et al, 2014), have been associated with functional and neuroanatomical abnormalities of the anterior cingulate and striatum (Gescheidt et al, 2013; Ruitenberg et al, 2018; Hlavatá et al, 2019; Kim and Im, 2019). Moreover, neuroimaging, brain-lesion, and stimulation studies have provided evidence for the association of the left inferior parietal cortex with covert attention to an upcoming movement (Rushworth et al, 2001a; Rushworth et al, 2001b; Rushworth et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, trait impulsivity without apparent ICD in PD patients has been proposed in several studies 14 17 . High impulsivity (HI) is a precursor of ICDs and can also lead to severe ICDs 18 , 19 . While HI may be within the spectrum of ICDs, the underlying pathophysiological mechanism differs between trait impulsivity and ICDs 20 .…”
Section: Introductionmentioning
confidence: 99%
“…For instance, ICD has been associated with increased connectivity between the left subthalamic nucleus and the left parietal operculum, whereas trait impulsivity has been associated with a weak connectivity between the left putamen and the right inferior temporal gyrus 21 . Other studies investigating cortical thickness, tractography, or functional MRI have also reported inconsistent results [5][6][7][19][20][21][22] . One of the causes is that impulsivity contains multifaceted constructs.…”
mentioning
confidence: 98%
“…Of the included 30 papers, 12 evaluated structural alterations [13][14][15][16][17][18][19][20][21][22][23][24], 12 evaluated functional alterations [25][26][27][28][29][30][31][32][33][34][35][36], and 6 included both structural and functional measures [37][38][39][40][41][42]. The study of Hammes et al [18] was included in the structural section only, as no between groups analysis was done in functional alteration analysis.…”
Section: Search Resultsmentioning
confidence: 99%
“…Three studies reported grey matter cortical volume using VBM [13,19,40]. Seven reports explored subcortical volumes for a set of a priori regions of interest using sMRI [14,15,18,24,[38][39][40]. Cth was reported in studies [14,15,18,19,23,24,[37][38][39], and subcortical white matter changes using DTI/DWI were described in further four studies [16,17,20,38].…”
Section: Dopaminergic Replacement Therapy-medicated Pd Patientsmentioning
confidence: 99%